2007
DOI: 10.1002/app.26146
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and dynamic mechanical properties of polyurethane‐modified epoxy composites filled with functionalized fly ash particulates

Abstract: Fly ash (FA) is a porous ceramic, which has proved to have some favorable functions. In this article, we have prepared a series of fly ash filled composites, where the polyurethane-(PU) modified epoxy (EP) was acted as the matrix. With the purpose of characterizing the effect of the content of PU in the matrices and the surfacetreatment (ST) of fly ash particulates on the dynamic mechanical properties of composites, Fourier transform infrared spectral analysis (FTIR), microstructure observation, impact propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…The O-H group in Si coupling agent condenses with O-H group of fly ash in an aqueous environment leading to the formation of covalent bond linkage for improving the resin wettability. The peaks at 2800 cm -1 are assigned to the C-H stretch in the propyl chain and the peak at1030 cm -1 is interpreted to the Si-O-Si bonds [14] .The FTIR spectra of sodium lauryl sulphate treated fly ash particles are shown in Figure 4c. It is observed that the peaks at the range of 1000-700 cm -1 are assigned for the vibration of Si-O and Al-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The O-H group in Si coupling agent condenses with O-H group of fly ash in an aqueous environment leading to the formation of covalent bond linkage for improving the resin wettability. The peaks at 2800 cm -1 are assigned to the C-H stretch in the propyl chain and the peak at1030 cm -1 is interpreted to the Si-O-Si bonds [14] .The FTIR spectra of sodium lauryl sulphate treated fly ash particles are shown in Figure 4c. It is observed that the peaks at the range of 1000-700 cm -1 are assigned for the vibration of Si-O and Al-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…2 chain extension by amine. The reason is that the N-H group and the carboxy group (C=O) of urethane has generated a spot of hydrogen bonds in our experiment, 27 which resulted in the absorption peak of N-H stretching shifted to low value. The band at 1745 cm À1 was C=O stretching of the urethane group, and the strong band at 1223-1267 cm À1 corresponded to the stretching vibrations of C=O combined with NH in all the spectra.…”
Section: Ir Spectramentioning
confidence: 97%
“…In the glassy region, the movement of chain segments is mostly "frozen" due to tight packing, so the material is prone to store more energy; this results in a high storage modulus [41]. The storage moduli of hybrid TCE + PTFE composites are high at −60 ∘ C and decreases as the temperature increases.…”
Section: The Effect Of Fiber and Filler Loading On Storage Modulus Lmentioning
confidence: 99%